Мехатронний комплекс для виробництва комбікорму: автоматизація, ефективність, інновації - Швець, Сергій; Shvets, Serhii; Калина, Вікторія Сергіївна; Kalyna, Viktoriia (Запоріжжя : Видавничий дім «Гельветика», 2025)
UA: У сучасних умовах розвитку сільськогосподарського виробництва питання забезпечення тварин якісними кормами є надзвичайно актуальним. Важливим складником кормової бази є комбікорми, що виготовляються з різних видів рослинної сировини, зокрема з кукурудзяних початків. Використання біологічно активних добавок дозволяє значно підвищити поживність кормів, їх засвоюваність та ефективність використання. У цьому контексті актуальним є розроблення нових підходів до виробництва комбікормів, зокрема шляхом впровадження мехатронних систем та автоматизованих технологій.Роботу зосереджено на дослідженні виробничих процесів створення комбікорму з кукурудзяних почат-ків з додаванням біологічно активних добавок, а також на розробленні мехатронного комплексу для забез-печення цього процесу. Проведено теоретичні дослідження, а також розроблено практичні рішення щодо впровадження автоматизованих комплексів для підвищення продуктивності та ефективності виробництва комбікормів. /// EN: In the context of modern agricultural production, the issue of providing animals with high-quality feeds is extremely relevant, as it directly affects animal productivity and health. An important component of the feed base is compound feeds, which are produced from various types of plant raw materials, particularly from corn cobs, which are affordable and efficient resources for feed production. The use of biologically active additives significantly improves the nutritional value of feeds, their digestibility, and ensures better conditions for animal development. These additives help increase the efficiency of feed utilization, reducing feeding costs and providing animals with the necessary nutrients for optimal growth and development.An essential condition for improving the production of compound feeds is the implementation of new approaches to their production. In this context, the development and application of mechatronic systems and automated technologies allows for high efficiency, reduced energy consumption, and improved product quality. Mechatronic complexes automate the processes of compound feed production, which helps reduce production time, improve the accuracy of ingredient dosing, and ensure consistent feed quality.This paper focuses on the study of production processes for compound feed made from corn cobs with the addition of biologically active additives to improve feed quality. Special attention is given to the development of a mechatronic complex to automate the production process. The paper includes theoretical studies on the impact of biologically active additives on the nutritional value of compound feeds, as well as practical solutions for implementing automated complexes in feed production. This will significantly increase productivity, efficiency, and ecological safety in the feed production process.
Mechatronic complex for feed production: automation, efficiency, innovations
Keywords: комбікорми; кукурудзяні початки; біологічно активні добавки; мехатронні системи; авто-матизовані технології; виробництво кормів; засвоюваність кормів; кормова база; compound feeds; corn cobs; biologically active additives; mechatronic systems; automated technologies; feed production; feed digestibility; feed base